Persepsi Dokter Klinik Dalam Menggunakan Rekam Medis Elektronik Berbasis Cloud Computing: Survei Penggunaan rekmed.com - Emi Azmi Choironi; Lukman Heryawan (Jurnal Ilmiah Informatika Global, 2023)
Background : The use of electronic medical records (EMR), including cloud computing-based EMR, is widely increasing. However, data regarding the perception of physicians using cloud computing-based EMR in Indonesia is still limited. Objective: This study aims to determine the perception of clinical doctors in using EMR based on cloud computing. Methods: This is a cross sectional study with a mixed-methods explanatory sequential design approach to determine the perception of clinicians in using cloud computing-based EMR. Qualitative analysis is used to support the depth of quantitative data analysis. Result: There are 10 private clinic doctors who participate. The average value of respondents' satisfaction after using cloud computing-based EMR is 7.4 from a scale of 1-10, with a median value of 8. In the analysis of interest in using cloud computing-based EMR in the long term, it was found that 30% of respondents said "yes", and 70% said "maybe". Qualitative data show that the problems in using EMR are the high price of the EMR system, security and privacy, the display is still limited, and the need for a stable internet network. Conclusion: The use of cloud computing-based EMR by clinicians still meet a number of obstacles. Further development is needed to increase the satisfaction and interest of doctors using RME based on cloud computingKeywords: electronic medical records, cloud computing, clinical physicians, perception